This can be solved by Newton's binomial formula
Tk+1 = (n k) a∧(n-k) b∧k k+1=7 => k=6, n=11 , a=-3x and b=-2y
T7= (11 6) (-3x)∧(11-6) (-2y)∧6 = (11*10*9*8*7)/(1*2*3*4*5) (-3x)∧5 (-2y)∧6
T7= 462 (-3x)∧5 (-2y)∧6
The correct answer is A.
Good luck!!!
Answer:
Step-by-step explanation:
Ok wait. Try add
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions here.
Matt's steps will be more complicated since Annie is using a program to do the constructions hers would probably be precise and easy.
I think it is tens or sum look up fractions place value and u will probable get it